Efeitos de diferentes formulações comerciais do herbicida Roundup® sobre a função cardiorespiratória de matrinxã, Brycon amazonicus (Teleostei, Characidae) - Anelli Junior, Luiz Carlos (2010)
Roundup is the herbicide most extensively used worldwide and its application in agricultural areas eventually contaminates the aquatic environment. However, given its importance as an herbicide, the literature on toxicological and ecotoxicological properties of the glyphosate in aquatic animals is scarce. In this research, control specimens of matrinxã, Brycon amazonicus, and specimens exposed to three different Roundup formulations (Original, WG and Transorb) at concentration of 5 mg.L-1 for 96 hours, showed the following results: change on the critical tension of O2 (PcO2) from 35 mmHg to 107 mmHg (Original group), to 114 mmHg (WG group), and to 94 mmHg (Transorb group). The Original and WG groups increased ed VO2 and V G in most of the PO2 tested while these parameneters decreased for Transorb group. Both VT and the relation V G / VO2 increased significantly in relation to the control group during progressive hypoxia, whereas EO2 was significantly reduced in all the three groups. The fR did not change significantly in relation to the group control whereas fH increased significantly in the Original group and did not show significant changes in the other groups. The tachycardia induced by the Original formulation could be related to a direct effect of glyphosate on the cardiac muscle, but could also be attributed to a stress-induced catecholamine release in response to the herbicide. On the other hand, the bradycardia observed in WG and Transorb formulation groups may be the result of the effect of inert ingredients found in their formulations and not only the glyphosate itself. Taken together, the results suggest possible structural changes in the gill filaments, reducing the efficiency of the gas exchanges. However, fR values did not change between groups exposed to herbicides, which indicates that all Roundup formulations may have reduced AchE activity, inhibiting tissues such as muscles and nervous system. Altogether, the results pointed that the effects of Roundup on B. amazonicus respiratory functions reduce its chances of survival, especially under conditions of environmental hypoxia.